Polyaniline/metal oxide nanocomposites: synthesis, characterization and study of their applications - Jamil, Sara Thualfuqar; Al-Abdaly, Basim Ibrahim (Iraqi Journal of Science, 2025)
This study included the synthsised of new nanocomposites using hydrothermal and sol-gel methods by preparing a mixture of metal oxides from their salts using the hydrothermal method, and then using the sol-gel method, the mixture of prepared metal oxides was reacted with polyaniline (as a substrate) prepared immediately through the polymerization of aniline (monomer). Nanocomposites consisting of polyaniline and various metal oxides (PANI-MO) were synthesized using a combination of hydrothermal and sol-gel techniques. This study employed metal oxides (MO) including zinc oxide (ZnO), copper oxide (CuO), and cobalt oxide (CoO). Metal oxides were added to the PANI to create nanocomposites nickelcobalt oxides (NiO: CoO) and nickel-copper oxides (NiO: CuO) were synthesized [NiO: CuO/PANI] and [NiO: ZnO/PANI] by the hydrothermal method and the sol-gel method, where a mixture of metal oxides is created and impregnated onto polyaniline, which serves as a support material. The nanocomposites were investigated using FT-IR, AFM, SEM and EDX techniques. Because of its cylindrical shape, variety in nature, and affordability, selective adsorption has been investigated by utilizing surfactants, which have made it unique and useful in a variety of applications. In this work, aniline was treated with sodium dodecyl sulfate (SDS) and hydrochloric acid (HCl) as a cross-linked method to change the composite of one polymer. SDS serves as an effective dispersing agent for aniline in aqueous solutions. The observed decrease in peak intensity may be attributed to the semi-crystalline nature of polyaniline (PANI) and the amorphous structure of the metal oxides (MO). Given these nano-characteristics of the synthesized nanocomposites, the research focused on exploring their potential applications in industrial and biological fields. Then next evaluated their industrial activities using anti-corrosion and biological processes using antioxidants. The effectiveness of the [NiO: CoO/ PANI] and [NiO: CuO/ PANI],[ NiO: ZnO/ PANI] nanocomposites were tested on antioxidant activity and showed a good scavenging percentage, where the highest antioxidant activity was obtained for the compounds [NiO: CoO/ PANI] and [ NiO: ZnO/ PANI]. Corrosion measurements revealed that the nanocomposite [NiO: CuO/ PANI] had the highest inhibition activity. PANI/CuO:NiO stands out as the most effective corrosion inhibition compound due to its superconductivity, strong protective layer formation, and synergistic effects between CuO and NiOleads to enhanced stability and corrosion resistance due to improved mechanical properties and chemical interactions.